Altered cerebral oxygen extraction and metabolism in preterm neonates and the relationship to anemia: A noncontrast MRI study - Zixuan Lin; Dan Wu; Dengrong Jiang; Hanzhang Lu; Ying Qi (Annals of the Child Neurology Society)
Abstract Objective The preterm brain is susceptible to structural injuries, which may be related to an imbalance between blood supply and oxygen metabolism. However, the effect of preterm birth on cerebral oxygen metabolism and its underlying mechanism have not been fully elucidated. The present study measured cerebral oxygen extraction and metabolism using noncontrast magnetic resonance imaging (MRI) methods in preterm neonates and examined its relationship with anemia of prematurity. Methods Fifty neonates with a gestational age of 28–42 weeks were enrolled. Cerebral oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) were measured with T2‐relaxation‐under‐spin‐tagging (TRUST) MRI, together with cerebral blood flow (CBF). Results We showed that CBF (p = 0.00021) and CMRO2 (p < 0.0001) increased with gestational age while OEF increased with postnatal age (p = 0.0013). Higher OEF was also associated with a higher Apgar score at birth (p = 0.039). Furthermore, hematocrit significantly mediates the increase of OEF with postnatal age (p < 0.001). Structural equation modeling analysis suggested a bidirectional relationship between CBF and CMRO2; both contributed to the changes in OEF. Interpretation These findings demonstrated an altered cerebral oxygen metabolism in preterm brain, suggesting a potential role of MRI–based oxygenation measurement in the assessment of transfusion and intervention for preterm neonates.